Antibodies against outer-capsid proteins of grass carp reovirus expressed in E. coli are capable of neutralizing viral infectivity - Shao, Ling (BioMed Central, 2011)
BACKGROUND: Grass carp reovirus (GCRV), which causes severe infectious outbreaks of hemorrhagic disease in aquatic animals, is a highly pathogenic agent in the Aquareovirus genus of family Reoviridae. The outer capsid shell of GCRV, composed of the VP5-VP7 protein complex, is believed to be involved in cell entry. The objective of this study was to produce a major neutralization antibody for mitigating GCRV infection. RESULTS: Recombinant plasmids of GCRV outer capsid proteins VP5 and VP7 were constructed and expressed in prokaryotic cells in our previous work. In this study, we prepared GCRV Antibody (Ab), VP5Ab and VP7Ab generated from purified native GCRV, recombinant VP5 and VP7 respectively. Immunoblotting analysis showed that the prepared antibodies were specific to its antigens. In addition, combined plaque and cytopathic effect (CPE)-based TCID(50 )(50% tissue culture infective dose) assays showed that both VP5Ab and VP7Ab were capable of neutralizing viral infectivity. Particularly, the neutralizing activity of VP7Ab was 3 times higher than that of VP5Ab, suggesting that VP7 might be a dominating epitope. Moreover, the combination of VP5Ab and VP7Ab appeared to enhance GCRV neutralizing capacity. CONCLUSIONS: The results presented in this study indicated that VP7 protein was the major epitope of GCRV. Furthermore, VP5Ab and VP7Ab in combination presented an enhanced capacity to neutralize the GCRV particle, suggesting that the VP5 and VP7 proteins may cooperate with each other during virus cell entry. The data can be used not only to further define the surface epitope domain of GCRV but may also be applicable in the designing of vaccines.